Forecasting Ecological Genomics: High-Tech Animal Instrumentation Meets High-Throughput Sequencing. - Aaron B A Shafer; Joseph M Northrup; Martin Wikelski; George Wittemyer; Jochen B W Wolf (PLoS Biology, 2016)
Recent advancements in animal tracking technology and high-throughput sequencing are rapidly changing the questions and scope of research in the biological sciences. The integration of genomic data with high-tech animal instrumentation comes as a natural progression of traditional work in ecological genetics, and we provide a framework for linking the separate data streams from these technologies. Such a merger will elucidate the genetic basis of adaptive behaviors like migration and hibernation and advance our understanding of fundamental ecological and evolutionary processes such as pathogen transmission, population responses to environmental change, and communication in natural populations.